Treatment of shoulder osteochondritis dissecans in the dog using asthroscopic procedure - Oliveira, G. G. S.; Padilha Filho, J. G.; Maniscalco, C. L. (Brazilian Journal of Veterinary Research and Animal Science, 2004)
The article has no abstract.